2022
DOI: 10.1088/1757-899x/1220/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

Study regarding the influence of geometrical characteristics of the distribution system on truck engines efficiency parameters

Abstract: The present paper aims to analyze the influence of certain parameters specific to the distribution systems on a truck engine performance. The research is focused on how the change in the shape of lobes of a camshaft can influence the vehicle functional parameters. It was considered a non-variable fuel distribution system which represents by itself the controlling part, needed to move the poppet valves in order to ensure engine operating cycles. There have been compared results obtained in the case of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Barothi et al [6] attempted to improve the engine performance by manipulating the camshaft lobe geometry. Results showed that changing the lobe lift height from 12 mm to 12.43 mm resulted in a 4.1% increase in cylinder filling efficiency during intake stroke.…”
Section: Introduction (Gi̇ri̇ş)mentioning
confidence: 99%
“…Barothi et al [6] attempted to improve the engine performance by manipulating the camshaft lobe geometry. Results showed that changing the lobe lift height from 12 mm to 12.43 mm resulted in a 4.1% increase in cylinder filling efficiency during intake stroke.…”
Section: Introduction (Gi̇ri̇ş)mentioning
confidence: 99%
“…The distorted geometry of the cams restricts the complete opening of the fuel injection valves and reduces the engine efficiency. 2 Although modern lightweight composites have revolutionary taken over the majority of automobile equipment, the least margin of compromise on the performance has restricted the integral parts of the engine to be preferably made of high-density ferrous materials.
Figure 1.Profile and nomenclature for different regions of the cams.
…”
Section: Introductionmentioning
confidence: 99%